Inhibition of translation of transforming growth factor-beta 3 mRNA by its 5' untranslated region. - Arrick, B A (1991)
We have cloned and sequenced the 5' untranslated region of the transforming growth factor-beta 3 (TGF-beta 3) mRNA as well as the adjacent genomic sequence. S1 nuclease analysis identified a single transcription start site. We have thus determined that the 5' untranslated region is about 1.1 kb long and contains 11 open reading frames. In vitro translation of the TGF-beta 3 precursor coding sequence was markedly inhibited by the presence of the 5' untranslated region. Similarly, when the 5' untranslated region of TGF-beta 3 was introduced upstream of the coding sequence of chloramphenicol acetyltransferase, in vitro translation was inhibited. Furthermore, upon transfection into 293 cells, chloramphenicol acetyltransferase expression was inhibited by the 5' untranslated region of TGF-beta 3. The degree of translational inhibition was inversely proportional to the amount of transfected DNA. Mutation analysis implicated multiple segments of the 5' untranslated region as contributing to the inhibitory effect. Deletion of much of the 5'-most 640 nucleotides, including 8 of the 11 upstream ATGs, relieved much but not all of the inhibitory influence of the 5' untranslated region of TGF-beta 3 mRNA. The two upstream open reading frames closest to the initiator codon for the TGF-beta 3 coding sequence also decreased translational efficiency, since mutation of either ATG resulted in increased translation. Transfection results with T47-D cells, a cell line which expresses TGF-beta 3 mRNA, were similar to those obtained with the 293 cell line. Thus, TGF-beta 3 mRNA is a recent example of an expanding group of growth-related mRNAs in which the 5' untranslated region contains upstream open reading frames and other sequences which inhibit translation.